THE EFFECT OF ETHANOL EXTRACT OF ANARCARDIUM OCCIDENTALE (CASHEW) STEM BARK ON SOME BIOCHEMICAL PARAMETERS OF ACETAMINOPHEN-INDUCED HEPATOTOXICITY IN RATS - Suurbaar, J.; Addai-Mensah, D.; Faisal, S.; Antwi, S.; Abaah, P.; Mohammed, Y. R. (UDS International Journal of Development, 2019)
The present study was designed to investigate some biochemical parameters associated with acetaminophen induced liver injury on rats treated with ethanolic stem-bark extract of Anacardium occidentale (EBAO). Qualitative studies on EBAO showed the presence of phytochemicals such as polyuronides, phenolic compounds and reducing sugars. Thirty (30) Wistar rats weighing 168.98 g to 292.91 g were grouped into five (I, II, III, IV and V) of six rats each. The curative model was applied. Liver Enzyme levels were measured prior to induction with acetaminophen in each group (I, II, III, IV and V) and the values were recorded as baseline enzyme or protein levels. Administration of 2500 mg/kg of acetaminophen caused a significant elevation in the levels of Aspartate aminotransferase (AST), Alanine aminotransferase (ALT) and Alkaline phosphatase (ALP) and decreased level of Albumin (ALB) in all the experimental rats compared to their baseline levels measured. Group I (treatment with silymarin) received 100 mg/kg of silymarin and distilled water respectively. Group II received normal saline as a control, Group III, IV and V were the plant extract treatment groups that were treated with 250 mg/kg, 500 mg/kg and 1000 mg/kg of the extract respectively for a period of five days. The experiment lasted for 10 days. There were significant (P<0.05) reduction of ALT, AST and ALP and an increased level of albumin during the five-day treatment of 500 mg/kg and 1000 mg/kg extract compared to their respective levels after induction. Keywords: Ethanolic stem-bark extract of Anacardium occidentale, Acetaminophine, Alanine aminotransferase, Aspartate aminotransferase, Alkaline phosphatase